SPEECH STYLES USED BY ACTORS AND ACTRESSES IN THE SENSE AND SENSIBILITY FILM - Kadang, Kristiani Irma; Burhamzah, Muftihaturrahmah; Nurfadhilah, Auliyanti Sahril (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study describes the types of speech styles used by the characters in the film Sense and Sensibility and the social factors that influence the use of these speech styles. This research aims to analyze the types of speech styles in film Sense and Sensibility based on the theory of Martin Joos (1967) and Holmes' theory (2017) to examine social factors that influence speech styles used by characters in Sense and Sensibility films. The research method used in this research is a qualitative descriptive method. Researchers analyzed the types of speech styles used by the characters. The research results shows there are 5 types of speech styles out of the 50 data found, there are formal style with 12 data representing 24% of all data, the consultative style with 5 data representing 10% of all data, the casual style with 26 data representing 52% of all data and intimate styles with 6 data representing 12% of all data, and finally frozen style with 1 data representing 2% of all data. There are four social factors that influence the use of speech styles by the characters, the four social aspects are participant, setting, topic, and function.